The Effect Of Audit Tenure And Auditor Rotation On Audit Quality (Empirical Study of Telecommunication sub-sector service companies on the IDX in 2013-2018) - Abdullah, Adam; Rahayu, Sri; Yetti, Susfa (Faculty of Economics and Business Universitas Jambi, 2023)
This study aims to see how the effect of audit tenure and auditor rotation on audit quality in telecommunication sub-sector service companies on the IDX. Audit tenure is measured by looking at the engagement period undertaken by KAP and its clients by using a value of 1 in the first year and adding one for the following years. Auditor rotation will be measured using a dummy scale that assesses whether or not there is a change of auditors in the audit process, and for audit quality in this study, it will be assessed through whether or not the hood is affiliated with the big four hood. This study uses a sample of telecommunication sub-sector service companies listed on the IDX. This study uses a nonprobability sampling method, while the sampling method to be used is purposive sampling. Nonprobability sampling means that it is a sampling technique that does not provide equal opportunities/opportunities for each element or member of the population to be selected as a sample. Purposive sampling technique is a sampling technique that aims to take samples from a population based on certain criteria. The sample used was 5 companies with a total of 30 samples. The data analysis technique in this study is descriptive statistics and logistic regression analysis. The results of hypothesis testing are as follows. to determine whether audit tenure, auditor rotation, simultaneous and partial effects on audit quality, and how much influence audit tenure and auditor rotation have on audit quality.